2021
DOI: 10.1111/btp.13050
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Andean uplift as an asymmetrical barrier to gene flow in the neotropical leaf‐cutting ant Atta cephalotes

Abstract: There is a wealth of evidence demonstrating that the Andean uplift has promoted allopatric diversification in a wide range of taxa (Hoorn et al., 2010;Pérez-Escobar et al., 2017;Salgado-Roa et al., 2018). These mountains reach their maximum complexity in northern South America (Colombia), forming a branch of three parallel mountain ranges separating flora and fauna in a North-South manner

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…cephalotes' dispersion from north to south (Muñoz-Valencia et al 2021). Although this initial study demonstrates a significant influence of the Andes on population divergence by the leafcutting ant at a phylogeographic scale, the role of local adaptation occurring at more regional scales across the Andes remains untested.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…cephalotes' dispersion from north to south (Muñoz-Valencia et al 2021). Although this initial study demonstrates a significant influence of the Andes on population divergence by the leafcutting ant at a phylogeographic scale, the role of local adaptation occurring at more regional scales across the Andes remains untested.…”
Section: Introductionmentioning
confidence: 85%
“…Mountain range of the Andean uplift in Colombia plays a major role as a geographic barrier to historical gene flow, restricting A. cephalotes' dispersion from north to south(Muñoz-Valencia et al 2021). By exploring a finer scale across the Western Mountain range and incorporating neutral genetic markers with environmental variables, we clearly show that observed genetic differentiation in A. cephalotes is mostly affected by a combined multifactorial effect of different isolating mechanisms mediated by the landscape complexity.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Mitochondrial markers are more suitable for investigating historical population events on large evolutionary scales, such as those of phylogeographical studies (Augustinos et al, 2014;Gyllenstrand & Seppä, 2003). For example, Muñoz-Valencia et al (2021) used this same mtCOI data to investigate the genetic structure of A. cephalotes from a larger geographic range, covering most of the distribution of the species from South and Central America. They found significant genetic differentiation, both at the regional scale and among populations within major regions.…”
Section: Spatial Differentiation At Regional and Population Levelsmentioning
confidence: 99%
“…Evolution under such environmental heterogeneity could act to shape patterns of gene flow (De Queiroz et al, 2017;Lee & Mitchell-Olds, 2011;Noguerales et al, 2016;Wang et al, 2013), which often produces more complex scenarios than genetic divergence due to IBD alone (Slatkin, 1993;Wright, 1943). For example, using mitochondrial DNA markers and a more extended sampling across Central and South America, we recently found that the eastern range of the Andes in Colombia plays a major role as a geographic barrier to historical gene flow, restricting the dispersion of A. cephalotes from north to south (Muñoz-Valencia et al, 2021). Although this initial study demonstrates the significant influence of the Andes on population divergence in the leaf-cutting ant at the phylogeographic scale, the role of local adaptation occurring at more regional scales across the Andes remains untested.…”
mentioning
confidence: 99%